Importación de joyas de plata desde Perú - Coronel Salguero, María Verónica (2017)
Informality is a problem that exists in most countries, especially in those oflesser development, causing tax evasion because there is no awareness of it,causing a negative effect on society.The importation of silver jewelry will allow us to know all the requirements,procedures, permits and obligations, so as to have a good management of allthe necessary steps between both countries, fulfilling the tax requirements of the country of destination, where they will be marketed. Technology has become one of the main components for the economy in the world, for both developed and developing countries. The negotiations are taking a turn due to the reach of the internet, and the ease of communication to do international business complying with the formalities of the Incoterms established between the parties. We will use information obtained from the country of origin of the merchandise,which will allow us to know the uses and benefits of the importation of silver jewelry, must take into account the tariff heading, the commercial benefits with both countries, through the agreement Of the CAN of which Ecuador and Peru are part.All the requirements of packaging, packing, and the correct use of pictograms will be known so that the jewels do not suffer any damages in the whole process of import, as the manipulation, logistics following the processes of suitable form. It is important to know the type of transport to use, because of its distance, time, value of the merchandise and insurance, each of the processes are important for the importation to be legal, obtaining a profit and covering the local demand.